2018
DOI: 10.1016/j.contraception.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Task-shifting the provision of DMPA-SC in the DR Congo: Perspectives from two different groups of providers

Abstract: ObjectivesTo document the experience of three groups of Family Planning service providers participating in task-shifting for the provision of subcutaneous depot-medroxyprogesterone acetate (DMPA-SC) at the community level in the DRC.Study designThis article compares results from interviews with DMPA-SC providers in two separate pilot studies: 1) 53 medical and nursing school students teaching women how to self-inject (2016–2017); and 2) 34 lay community health workers providing DMPA-SC in rural areas of Lualab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 9 publications
(12 reference statements)
0
23
0
Order By: Relevance
“… 2018 ; Hernandez et al. 2018 ). Self‐care options such as self‐injection of Sayana Press have also been shown to be acceptable in other settings (Cover et al.…”
Section: Discussionmentioning
confidence: 99%
“… 2018 ; Hernandez et al. 2018 ). Self‐care options such as self‐injection of Sayana Press have also been shown to be acceptable in other settings (Cover et al.…”
Section: Discussionmentioning
confidence: 99%
“…Results from the companion article Task-shifting the provision of DMPA-SC in the DR Congo: perspectives from different groups of providers showed that CHWs were not satisfied with the compensation received [ 14 ]. Under this pilot, CHWs operated on a volunteer basis.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 34 CHWs participated in the pilot. The average age of participating CHWs was 42.2 years, 52.9% ( n =18) were female, almost three quarters were married ( n =25), and all but one CHW had children (mean number: 5.8 children) [14] .…”
Section: Methodsmentioning
confidence: 99%
“…Hernandez and colleagues interviewed two cadres of community-level providers: medical and nursing students who administered DMPA-SC in a community setting or who taught women how to self-inject and CHWs who provided DMPA-SC in rural areas. Over 90% of these providers reported being comfortable or very comfortable interacting with clients, and more than three quarters of them were very comfortable performing an injection [8]. In the same study, Mwembo and colleagues assessed the acceptability and feasibility of DMPA-SC among 252 women on the initial injection date and 3 months later.…”
Section: Overview Of Key Findingsmentioning
confidence: 99%